âUm som meio fanhoso, mas gostoso de ouvirâ: radio and music culture in Fortaleza(1932-1944) - Emy FalcÃo Maia Neto (2010)
This research tried to bring to the debate the story of the early years of radio in Fortaleza (1932-1944). Throughout three chapters this paper intends to show how the relations of feelings that gathered individuals to radio "invented" the "spot" of radio in the city and changed their relation with music. This paper analyzes questions related to musical sociability, the performance of those involved with the station during the period studied, the programming that was conveyed at the time, the uses and the tensions that surrounded these "consumption" of radio in Fortaleza